A comparative assessment of apical debris extrusion by various glide path establishing endodontic instruments: An in vitro study - V P Anshida; M E Sudhanva; R Vikram; Vishwas S Gowda (Wolters Kluwer Medknow Publications, 2021)
Introduction: A reproducible glide path provides guidance to fulfil the mechanical objective of cleaning and shaping root canals with minimal procedural errors. Debris expelled during this procedure contributes to inter-appointment flare-up. The objective of this in vitro study was to estimate and compare the quantity of debris extruded by; hand, rotary and reciprocating glide path preparation instruments. Materials and Methods: Seventy-five human single rooted, matured mandibular incisors with single canal and comparable lengths were randomly allocated into three groups (n = 25): group A - Stainless steel (SS) K-file (No 15), Group B - ProGlider, and Group C -WaveOne Gold Glider. Customized apparatus using Meyers and Montgomery method was utilized to accumulate the debris expelled apically in the Eppendorf tubes weighed priorly in digital analytical balance of 10−6 g accuracy. All groups were instrumented as per the manufacturer's guidelines. After instrumentation, teeth were detached from the Eppendorf tubes and tubes incubated at 70°C for 5 days to vaporize the irrigating solution. The tubes with dry debris were later weighed in the same weighing balance. The collected information was analyzed by one-way ANOVA and Tukeys honest significant difference post hoc test at significance level (P < 0.05). Results: The ProGlider group expressed statistically significant result with least quantity of extruded debris in the comparison to other groups (P < 0.0001). The SS group and WaveOne Gold Glider group exhibited no significant difference, but the debris expelled was less for WaveOne Gold Glider group than SS group. Conclusion: Glide path preparations with rotary ProGlider resulted in the minimal extrusion of debris in comparison to the reciprocating WaveOne Gold Glider and the manual stainless-steel K-files.